Non-linear M -sequences Generation Method - Z. R. Garifullina; M. A. Ivanov; V. E. Ryabkov; I. V. Chugunkov (Безопасность информационных технологий, 2011)
The article deals with a new method for modeling a pseudorandom number generator based on R-blocks. The gist of the method is the replacement of a multi digit XOR element by a stochastic adder in a parallel binary linear feedback shift register scheme.